Dialectic walk through the sciences - Pérez Martínez, María Eugenia (2015)
The book deals with the nature of the science and the research, especially in their unusual and paradoxical facets: science and research become accessible by means of exemplification. The book means a review in dialectics, as long as this can be considered a general framework in which evolutionary phenomena are registered. Also, it provides with a new principle of dialectics "extracted from phenomena of deterministic chaos". It presents various reading levels.